Edukasi dan Pelatihan Pembuatan Pupuk Organik Cair Berbasis Limbah Air Cucian Beras - Wazdi, Adi Indradi; Putri, Renny Anggraeni; Permana, Gilang; Akmila, Dyna (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
Agriculture is the utilization of natural resources related to land, plants, animals (including fish) to produce human needs (both food, clothing, shelter and feed). One of the important components in agriculture, especially in land cultivation, is fertilizer. The problem that often arises among the farmers in Cisitu Village, Cisitu District, Sumedang Regency is the high price of chemical fertilizers sold, which often forces them to borrow money from financial institutions, ultimately putting a burden on themselves. Therefore, it is necessary to socialize the making of liquid organic fertilizer so that the community, especially farmer groups, are able to make their own fertilizer. The materials needed are affordable and easy to obtain. The main ingredient of making this fertilizer is rice washing water waste which is then added with em4 and brown sugar. The method used is Participatory Action Research (PAR) through 3 stages (planning, execution, results, and evaluation). As a result of this socialization, participants were able to understand how to make and apply liquid organic fertilizer to plants.